1980
DOI: 10.1136/ard.39.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death in patients with rheumatoid arthritis with particular reference to azathioprine.

Abstract: SUMMARY Three hundred and eleven patients with classical or definite rheumatoid arthritis were observed over an 11-year period. This group is of particular interest since 214 patients were given cytotoxic therapy, 203 were treated with azathioprine (52 of these also received chlorambucil or cyclophosphamide), and 11 were treated with cyclophosphamide or chlorambucil alone. Forty-six patients died. This is an excess mortality compared with the expected rate for the general population matched with respect to ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(33 citation statements)
references
References 24 publications
3
27
0
3
Order By: Relevance
“…The study verified the increase of the overall death rate previously reported in several studies on patients with RA (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)44). In line with other reports, death was predicted by high age at disease onset and male sex (31,42,164) and cardiovascular event (165).…”
Section: Epidemiologysupporting
confidence: 80%
See 1 more Smart Citation
“…The study verified the increase of the overall death rate previously reported in several studies on patients with RA (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)44). In line with other reports, death was predicted by high age at disease onset and male sex (31,42,164) and cardiovascular event (165).…”
Section: Epidemiologysupporting
confidence: 80%
“…Generally, hospital-based materials (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) reveal standardized mortality ratios (SMR) in the range of 1.3-2.5 but figures as high as 3.0 have been reported (39)(40). In population-based studies the excess death rates are somewhat lower (SMR 1.16-1.37), but still significantly higher than in controls (41,42), except for in one study (43).…”
Section: Life Expectancymentioning
confidence: 99%
“…Likewise, entry into the cohorts in these studies was set to the date of the first discharge with RA, which may not necessarily equate to the date of diagnosis of RA. Although there are studies using other designs and follow up methods, [18][19][20][21][22][23] these have often been limited to a few hundred patients diagnosed and/or followed up before the 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…In Zusammenhang mit Azathioprin konzentrieren sich die Hinweise vor allem auf Lymphome, die sich vorzugsweise im ZNS manifestieren [21,25,27]. Während sich unter der durch Azathioprin bedingten Immunsuppression nach Organtransplantationen gehäuft PZNSL entwickeln [29], ist wenig über den kausalen Zusammenhang zwischen Azathioprin und PZNSL in der Behandlung von Autoimmunerkrankungen bekannt.…”
Section: Pznsl Unter Azathioprinunclassified
“…Die Kasuistik über ein PZNSL unter der Behandlung einer Autoimmunerkrankung mit Azathioprin bestätigt die bekannten Kasuistiken und ergibt einen weiteren Hinweise darauf, dass Thiopurine das Risiko von Malignomen, insbesondere von zerebralen Lymphomen, erhöhen [21,25,27].…”
Section: Diskussionunclassified